Relationship between the three dimensions of institutes required for entrepreneurship development - Saurabh Sonkar; Ashoke Kumar Sarkar (Goodwood Publishing, 2020)
Purpose: The study was conducted to formulate the relationship between the three dimensions of institutes, namely cognitive, regulative and, normative dimensions of institutes. The model was formulated using SmartPLS 3. Research Methodology: In this study, the Five-point Likert scale was used and the data were collected from postgraduate students in two states of Uttar Pradesh and Jharkhand. SmartPLS 3 was used to formulate the model and establish the relationship between the three dimensions of institutes. Results: There exists a positive relationship between